Staging of esophageal cancer using PET/MRI: a systematic review with head-to-head comparison - Alisa Mohebbi; Saeed Mohammadzadeh; Zahra Moradi; Afshin Mohammadi; Hossein Poustchi; Seyed Mohammad Tavangar (BMC Medical Imaging)
Abstract Purpose To evaluate the staging performance of positron emission tomography/magnetic resonance imaging (PET/MRI) for confirmed esophageal cancer based on the TNM classification system as well as compare it to other alternative modalities (e.g., endoscopic ultrasonography (EUS), computed tomography (CT), MRI, and PET/CT) in a full head-to-head manner. Methods Protocol was pre-registered a priori at ( http://osf.io/6qj5m/ ). We searched PubMed, Web of Science, Embase, and Cochrane Library for studies until September 10, 2024. The risk of bias was assessed using Modified Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) and Quality Assessment of Diagnostic Accuracy Studies–Comparative (QUADAS-C). The classification performance of PET/MRI in T, N, and M staging of esophageal cancer and resectability status were evaluated and compared to other relative modalities. Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) was used for certainty evaluation. Results Nine studies were included with 245 esophageal cancer patients. For T, N, and M staging, PET/MRI showed 9.1%, 2.0%, and 10.7% upstaging than the histopathological evaluation while these numbers were 19.4%, 12.4%, and 5.3% for downstaging. For direct comparison with PET/CT, PET/MRI showed 0.7% and 5.6% less downstaging and upstaging for N staging and 2.5% and 4.0% for M staging. As for predicting resectability status, pre-ADCmean and post-ADCmean were promising, unlike other parameters (i.e., ΔADCmean, pre-SUVmax, post-SUVmax, and ΔSUVmax). Conclusion With protocol adjustments, PET/MRI might be utilized in the future for preoperative staging of esophageal cancer. Clinical trial number N/A.